AN INVESTIGATION OF STUDENTS’ UNDERSTANDING AND BELIEF ON MATHEMATICAL PROBLEM SOLVING IN THE CONTEXT STRUGGLE MONUMENT - Arifin, S; Zulkardi, Zulkardi; Putri, R I I; Hartono, Y; Susanti, E (Sriwijaya University Learning and Education International Conference, 2018)
This research is a qualitative research that aims to describe students 'understanding of problems solving the problem and also to describe students' belief about their solution to problems solving. The subjects of this study were 6 students in SMP Palembang that consisting of 2 high-ability students, 2 medium-skilled students, and 2 low-ability students. Data obtained through written test and interview. The results of this study indicate that only high-ability and medium-skilled students are able to understand the problem. This is illustrated by the verbal arguments given by the students when asked to explain the problem situation and to represent it in non-formal form. If viewed from the aspect of students' beliefs about their solution in problem-solving, seen almost all students are not sure with the answer he wrote. This is due to the limited ability of mathematical students and the lack of knowledge of students in writing mathematical models or confusion in using appropriate strategies to solve the problem.